Technical-tactic performance level of a female Caçador female youth futsal team - Calderan, Bruna Rafagnin (2022)
The female futsal comes in a steadily increasing. Starting from that, for this evolution to continue in this great ascendancy, the technical and tactical levels of the athletes must be raised, keeping in mind that these are the main characteristics for the accomplishment of a game of futsal, so the match occurs with high intensity, to that, a high percentage of possession of ball, that way goals and big matches will be realized. Based on this, the main objective of the present study was to verify the level of technical-tactical performance of young women's indoor soccer players in Caçador-SC of the sub-16 category. A field survey was carried out with 13 female futsal athletes from Caçador-SC from 14 to 16 years old, with a mean age of 15.2 years, who participated in the selective phase of the Santa Catarina Youth Games (OLESC). The level of performance of the athletes was evaluated in the formal game environment through the Individual Technical-Tactical Performance Evaluation Instrument (IADFutsal) adapted after the filming of two team matches in the competition. The staff showed a good level of assertiveness in the pass and reception grounds. In the disarmings, one can see that the greatest occurrence was to recover or take the ball. Regarding the finalizations the team built good chances of goal, but the achievement in goal showed a low average. Thus, through technical-tactical analysis it can be seen that the U16 team of Hunter has to improve the levels of conversion in goals, although tactically manage to fulfill its functions within the game.